The feeling of threat and stress: the mediating role of social ties in the workplace on the example of the mine rescuer occupation - Marta Stasiła-Sieradzka; Elżbieta Turska (Nofer Institute of Occupational Medicine, 2019)
Background Working in high-risk occupations is associated with the feeling of threat and stress. The aim of the research conducted from December 2016 to May 2017 was to examine the relationship between these variables in the group of mine rescuers. It was assumed that the quality of social ties with co-workers would act as a mediator of the assumed relationship. Material and Methods The sample consisted of 232 mine rescuers employed in emergency stations in Poland. The risk assessment at work was determined using Kwestionariusz poczucia zagrożenia w pracy (The Feeling of Threat at Work Questionnaire) by Mamcarz; Kwestionariusz poczucia stresu (The Feeling of Stress Questionnaire) by Plopa and Makarowski was used to study the feeling of stress, and the quality of social ties was measured using Skala więzi społecznych (The Social Ties Scale) by Skarżyńska. Results A negative relationship was observed between the feeling of threat and the level of the experienced stress. The sense of social ties with co-workers acts as a mediator in the relationship between these variables. Conclusions Social ties reduce stress caused by the feeling of threat, and they are also an important factor supporting the coping with negative emotions. The obtained results make it possible to present practical recommendations, aimed mainly at strengthening the adaptation and integration activities in teams carrying out their tasks in hazardous conditions. The authors of the study point out that these activities should concern primarily the following 3 areas: the adaptation of new members of the group, the strengthening of positive relationships in teams, and support in a traumatic situation during convalescence. Med Pr. 2019;70(3):295-304